PLANT DIVERSITY IN HOMEGARDENS AND THEIR USE VALUE IN TWO VILLAGES OF RUPANDEHI DISTRICT, WESTERN NEPAL - Srish, Okmaya; Pokhrel, Chandra P.; Yadav, Ram Kailash P. (Ecoprint: An International Journal of Ecology, 2013)
Homegardens play significant role in the livelihood of the rural people. The cultivation of different plants in homegardens for self-sufficiency has a long tradition worldwide, but knowledge about homegardens in Nepal is meager. To analyse this more deeply, cultivated plants of 15 homegardens were surveyed in two Village Development Committees (VDCs) in Tarai of Westren Nepal, viz. Anandavan and Karahiya VDCs. This study mainly focuses on the plant species diversity and their use values. Mostly perennial plants were included in the study. The plant studied in the homegardens included those which are used as fruits, fodder, medicine, nut and others. In Total, 31 plant species were found in the studied homegardens. Species diversity in the home gardens of Anandavan VDC was higher (H’=2.45) than that of Karhiya VDC (H’=2.19). The evenness of species, however, was not different in the homegardens of two VDCs. DOI: http://dx.doi.org/10.3126/eco.v18i0.9415 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 85-90 Uploaded date: 12/22/2013